Optimization of Production Process by Applying Theory of Constraint (TOC) at CV. Wijaya Mandiri Label - Agraprana, Al Aileen; Donoriyanto, Dwi Sukma (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
CV. Wijaya Mandiri Label is a company engaged in the printing industry sector located in Sidoarjo which provides printing services inside and outside Sidoarjo. In the production process, problems arise after several years of operation at work stations that cause bottlenecks in the production capacity of bontax and OPP sticker printing, thus hindering the production process to run optimally. This resulted in an inefficient sticker production process in meeting targets that made throughput not optimal. To overcome these problems, researchers conducted research that explored the use of Theory of Constraints (TOC) and supporting methods, namely linear programming, to optimize the company's production process and analyze data on working hours and product production demand. From the results of the research, it was concluded that the company experienced Capacity Constraints which caused bottlenecks at the fourth work station in the last six months. After exploiting the constraints on the bottleneck workstation, throughput is obtained using a linear programming calculation formulation with the results of x1= 0 and x2 = 3,948.47 amounting to IDR16,781,000 in WinQSB software. The final stage of constraint elevation is carried out by allocating operators to bottleneck work stations and obtaining an increase in throughput of IDR6,322,300 or a percentage increase of 27.4% using WinQSB software.